Fundamentals of Entrepreneurship (ENT 300) : Anggun Beach Villa Café & Guest House / Dayang Ernie Nurfarah'ain Awang Ahmad ...[et al.] - Awang Ahmad, Dayang Ernie Nurfarah'ain; Lamba, Jeffery Das; Nasir, Nas Hanini; Achai, Ammiliaanne; Sulaiman, Ayu Farzilawanee; Hamdan, Norazwa (2016)
The business is operate 7 days in a week. They provide accommodation, foods services and outdoor activities to the customer. The place used for relaxation or recreation, attracting visitors for vacations or tourism. Waking up in a place where your first glimpse of the day is an endless horizon of turquoise and blue, dotted with lush tropical islands.